1967
DOI: 10.1002/aja.1001210302
|View full text |Cite
|
Sign up to set email alerts
|

Local uterine regulation of the corpus luteum

Abstract: In order to determine if the well known uterine inhibition of the guinea pig corpus luteum is a local effect, a series of partial hysterectomies were performed. Some groups were subjected to one-half or three-fourths hysterectomies alone, while in others one ovary was also removed on either the side retaining some or the side losing all uterine tissue. In addition, two groups in which all ovarian and uterine tissue was preserved were subjected to unilateral or bilateral complete surgical separation of all comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…This conclusion is in accord with the findings of experiments involving removal of the uterus and the introduction of endometrial extracts or transplants (see Bland & Donovan, 1966a) and with those experiments revealing that partial hysterectomy in the sow and guinea-pig respectively may extend luteal function in the ovary on the operated side while not affecting the contralateral ovary (Du Mesnil du Buisson, 1961;Fischer, 1965). In the guinea-pig, Fischer (1965) noted that after hemi-hysterectomy the corpora lutea were maintained for extended periods in the ovary deprived of uterine influence. The volume of the corpora lutea in hemihysterectomized guinea-pigs has been measured by Bland & Donovan (1966b), who found that the corpora lutea in the ovary adjacent to the intact horn regressed normally while those in the ovary on the operated side enlarged.…”
supporting
confidence: 86%
“…This conclusion is in accord with the findings of experiments involving removal of the uterus and the introduction of endometrial extracts or transplants (see Bland & Donovan, 1966a) and with those experiments revealing that partial hysterectomy in the sow and guinea-pig respectively may extend luteal function in the ovary on the operated side while not affecting the contralateral ovary (Du Mesnil du Buisson, 1961;Fischer, 1965). In the guinea-pig, Fischer (1965) noted that after hemi-hysterectomy the corpora lutea were maintained for extended periods in the ovary deprived of uterine influence. The volume of the corpora lutea in hemihysterectomized guinea-pigs has been measured by Bland & Donovan (1966b), who found that the corpora lutea in the ovary adjacent to the intact horn regressed normally while those in the ovary on the operated side enlarged.…”
supporting
confidence: 86%
“…The time of survival of corpora lutea in the ipsilateral ovary is controlled by the uterine horn in sheep (Inskeep & Butcher, 1966; Thorburn & Nicol, 1971;McCracken et al, 1972), guinea-pigs (Bland & Donovan, 1966;Fischer, 1967) and cows (Ginther, Woody, Mahajan, Janakiraman & Casida, 1966). In pigs, however bilateral regression occurs after semihysterectomy (Spies, Zimmerman, Self & Casida, 1958), although if as little as one-quarter of one horn is left intact, the corpora lutea on the opposite side do not regress (du Mesnil du Buisson, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with partial hysterectomy have shown that this luteolytic action acts on a local basis such that each uterine horn influences only its neighbouring ovary (Fischer, 1965(Fischer, , 1967Bland & Donovan, 1966a; Barley, Butcher & Inskeep, 1966). Experiments with unilateral uterine distension have sub¬ stantiated this fact (Bland & Donovan, 1965, 19666;Ginther, Mahajan & Casida, 1966a, 19666).…”
Section: Introductionmentioning
confidence: 99%